INTROVERT STUDENTS’ PERFORMANCE ON ESSAY WRITING - Novi Rahmania (PROSIDING NATIONAL CONFERENCE FOR UMMAH, 2020)
This research will investigate the performance of Introvert students on their way in writing the Essay. This research object was the 3rd semester of EFL students in a private university in Surabaya academic year 2019-2020. This study used descriptive qualitative. For the data collection, this research used questionnaire and documentations as the instruments. The students are all had Writing III as the subject on that semester, totally 22 students were be the sample. This research also discussed the factors related such as what are the things influence this type of personality in writing an Essay.